Coefficient inequality for certain subclasses of univalent functions - Aini Janteng; Suzeini Abdul Halim; Maslina Darus (Pushpa Publishing House, 2005)
Let f (z)= z+ ∑_(n=2)^∞▒〖a_n z^n 〗 an analytic and univalent function in the unit disk D = {z├∶┤|├ z┤| z < ├ 1}. The purpose of the present paper is to introduce the functional |a_4-μa^(2/3) | when µ is real. We give sharp upper bounds for |a_4-μa^(2/3) | for certain subclasses of univalent functions. The results obtained are sharp.